1995
DOI: 10.1161/01.cir.92.6.1531
|View full text |Cite
|
Sign up to set email alerts
|

Left Heart Obstructive Lesions and Left Ventricular Growth in the Midtrimester Fetus

Abstract: The potential for the in utero development or progression in severity of left heart obstruction and hypoplasia in left heart obstructive lesions necessitates serial prenatal study in affected fetuses carried to term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
1
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(141 citation statements)
references
References 28 publications
2
134
1
4
Order By: Relevance
“…Furthermore, obstructive lesions can develop or progress as pregnancy advances and may not be recognisable around 20 weeks of gestation. 32,33 We believe that another factor that adds to the persistent low detection rates is the fact that training programmes do not sufficiently teach how to diagnose those anomalies in fourchamber and sagittal views. The difficulty in the diagnosis of anomalies of the aortic arch has been widely acknowledged, 34 yet this study showed a significant increase in the detection rate of coarctation of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obstructive lesions can develop or progress as pregnancy advances and may not be recognisable around 20 weeks of gestation. 32,33 We believe that another factor that adds to the persistent low detection rates is the fact that training programmes do not sufficiently teach how to diagnose those anomalies in fourchamber and sagittal views. The difficulty in the diagnosis of anomalies of the aortic arch has been widely acknowledged, 34 yet this study showed a significant increase in the detection rate of coarctation of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…In at least some cases, the fetus is identified as having aortic stenosis at midgestation, which then evolves into HLHS during the second half of pregnancy (28). Flow abnormalities have been implicated in CVM.…”
Section: Discussionmentioning
confidence: 99%
“…Left and right ventricular end-systolic and end-diastolic diameters and wall thickness were measured from M-mode tracings or 2-dimensional images as previously described. 6,7 Measurements obtained in the fetal CM cases were compared with values obtained in 55 normal pregnancies. Left and right ventricular systolic function was evaluated by calculating the shortening fraction (SF).…”
Section: Methodsmentioning
confidence: 99%